[PP.09.33] THE EFFECTS OF SMOKING ON CENTRAL BLOOD PRESSURE IN MIDDLE-AGED AND ELDERLY JAPANESE INDIVIDUALS. (September 2017) - Nagatomo, N.; Miyai, N.; Okano, Y.; Morishita, M.; Uchikawa, Y.; Yamamoto, M.; Shimabukuro, M.; Mure, K.; Utsumi, M.; Takeshita, T.; Arita, M.
Abstract : Objective: The aim of this study was to investigate the effect of smoking habits on central blood pressure in a population-based sample of middle-aged and elderly individuals. Design and method: A total of 406 normotensive and untreated hypertensive (stage-1) individuals (mean age; 59 ± 10 years) without a history of cardiovascular disease, renal disease and arteriosclerosis obliterans was recruited for this study. When the subject was in a comfortable seated position the peripheral brachial pressures were measured, and then the brachial waveform was captured by a standard brachial cuff (SphygmoCor XCEL) and the central aortic pressures were estimated using a generalized transfer function. Smoking status was determined by questionnaire. Current smokers and former smokers were asked how many cigarettes they smoked per day and the number of years spent smoking. Brinkman Index (BI) values were calculated as the number of cigarettes smoked per day multiplied by the number of years of smoking. Results: The subjects were divided into subgroups according to cumulative number of cigarettes smoked; never-smokers (N = 292), mild-to-moderate smokers (BI of < 800 per lifetime, N = 64), and heavy smokers (BI of > = 800 per lifetime, N = 50). Central systolic pressure was higher in both heavy smokers (123mmHg, P < .001) and mild-to-moderate smokers (117mmHg, P = .070) than those in never-smokers (112 ± 14mmHg) after adjustment for sex, age, and body mass index (p for trend<.001). This dose-response increase by smoking status was not clearly demonstrated in brachial systolic pressure. A stepwise multiple regression analysis revealed that the heavy smoking (β = .192, P < .001), age (β = .231, P < .001), body mass index (β = .278, P < .001), and LDL cholesterol (β = .099, P = .028) were selected as significant determinants of central systolic pressure independent of sex. Conclusions: These results suggest that smoking habits may have greater impact on central aortic pressure than peripheral brachial pressure and hence could be identified by abnormal increases in central systolic pressure and wave reflection even before clinical manifestation of hypertension.